Pengaruh Sosialisasi Kegiatan Budidaya Lele Melalui Akuaponik Terhadap Pemberdayaan Masyarakat Gadel - Putri Aulia Agustiawati; Marseto; Fauziatul Laily Nisa (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Gadel Village is an area located in RW 06, Karangpoh Village. This Gadel village has limitations in empowering its community. This community service activity has the main goal of optimizing community empowerment in Gadel Village through socialization of catfish cultivation activities with an aquaponic system. This socialization concept will emphasize the independence of the Gadel village community to be able to achieve prosperity, and their goals are implemented through aquaponic-based cultivation activities. The problem raised in this research is the influence of aquaponics socialization on the empowerment of the Gadel community. The purpose of this study was to determine how the influence of aquaponics socialization on the empowerment of the Gadel community. The research method used in this research is descriptive qualitative method by conducting data collection techniques such as observation.